Perancangan Media Pembelajaran Membaca untuk Anak Prasekolah (TK) Berbasis Multimedia - Amelia Permata Sari (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The author discusses this title on the background that preschool children in the process of learning to read have difficulty understanding reading teaching materials, one of which is about letter recognition because this is a new experience. Based on these problems, the author aims to design/design a reading learning media for preschoolers (kindergarten) based on Multimedia using Adobe Flash. The method used in the research is the research and development (R&D) method, which is a research method used to produce certain products and test the effectiveness of products with Blackbox. The research results of this reading learning media design for preschoolers (kindergarten) are: (1) This reading learning media uses the Luther-Sutopo multimedia development model which is carried out in six stages, namely the concept, design, material collecting, assembly, testing and distribution stages. (2) The final result of this reading learning media design is a compact disk (CD) that can be run using media on a computer and does not require another system to run it.